Repeated sprint ability but not neuromuscular fatigue is dependent on short versus long duration recovery time between sprints in healthy males. Issue 6 (June 2017) - Monks, Michael R.; Compton, Chris T.; Yetman, Joseph D.; Power, Kevin E.; Button, Duane C.
Abstract: Objectives: During maximal intensity leg cycling sprints, previous research has shown that central and peripheral fatigue development occurs with various (<30 s) short-duration recovery periods between sprints. The aim of the current study was to compare the development of neuromuscular fatigue during maximal intensity lower-body sprints interspersed with short and longer duration recovery periods. Design: Crossover study. Methods: Ten participants completed 10, 10 s sprints interspersed with either 30 or 180 s of recovery. Peak power outputs were measured for each sprint. Maximal force, voluntary activation (VA) and evoked contractile properties of the knee extensors were measured at pre-sprint 1, post-sprint 5 and post-sprint 10. Perceived pain was also measured immediately following each sprint. Results: Peak power output was significantly lower by 16.1 ± 4.2% ( p  < 0.001) during sprint 10 with 30 compared to 180 s of recovery. Irrespective of recovery time, maximal force, VA and potentiated twitch force decreased by 26.7 ± 7.2% ( p  < 0.005), 5.8 ± 1.2% ( p  = 0.025), 38.7 ± 6.1% ( p  = 0.003) respectively, from pre-sprint 1 to post-sprint 10. MVC and PT decreased by 17 ± 4% ( p  < 0.003) and 23 ± 9% ( p  < 0.002) respectively, from pre-sprint 1 to post-sprint 5. Conclusions: Although decreases in peak power and increases in perceived pain were greater when sprints were interspersed with 30 compared to 180 s of recovery, the development of neuromuscular fatigue of the knee extensors was similar. The results illustrate that peripheral fatigue developed early whereas central fatigue developed later in the sprint protocol, however the effect of recovery time on neuromuscular fatigue could be task specific.